Stable oxygen and carbon isotope composition of holocene mytilidae from the camarones coast (Chubut, argentina): Palaeoceanographic implications - Boretto, Gabriella Margherita (2020)
The stable isotope composition of living and of Holocene Mytilidae shells was measured in the area of Camarones (Chubut, Argentina). The most striking results were the high δ18 O values measured in samples older than ca. 6.1 cal ka BP. In the younger samples, the δ18 O values remained substantially stable and similar to those of living specimens. Analysis of the data revealed the possibility for this isotopic shift to be driven mainly by changes in temperature probably accompanied by minor changes in salinity, suggesting cooler seawater before 6.1 cal ka BP, with a maximum possible temperature shift of ca. 5◦ C. A possible explanation of this change can be related to a northward position of the confluence zone of the Falkland and Brazilian currents. This is consistent with the data obtained in marine cores, which indicate a northerly position of the confluence in the first half of the Holocene. Our data are also in line with the changes in wind strength and position of the Southern Westerlies Wind, as reconstructed in terrestrial proxies from the Southernmost Patagonia region.